THE USAGE OF WEB APPLICATIONS IN ENGLISH LANGUAGE LEARNING - Olena Shcherbakova; Taisiia Baranenko (Scientific Journal of Polonia University, 2024)
The purpose of this article is to examine the use of web applications and artificial intelligence (AI) in learning English as a Second Language (ESL). In this article, we analyze the impact of web applications such as Genially, Quizlet, ESL Games, and Miro on the language learning process, which offer innovative approaches for teachers and students, providing interactive and effective learning experiences. The article also explores the prospects of Artificial Intelligence in the ESL field, presented through tools like ChatGPT and AI-Twee, which open up new possibilities for personalized learning and automated assessment. With this work, we aim to encourage more educators to use these technologies to create adaptive lesson plans, interactive tasks, and effective knowledge assessments. In turn, students will have the opportunity to improve their language skills through personalized recommendations, interactive games, and automated grading systems. It is quite important to note that the combination of web applications and AI holds significant potential for enhancing the efficiency and quality of English language learning, making it more adaptive, interactive, and accessible for students worldwide.